Pulmonary findings in infants with cystic fibrosis during the first year of life: Results from the Baby Observational and Nutrition Study (BONUS) cohort study. Issue 5 (22nd January 2019) - Goetz, Danielle; Kopp, Benjamin T.; Salvator, Ann; Moore‐Clingenpeel, Melissa; McCoy, Karen; Leung, Daniel H.; Kloster, Margaret; Ramsey, Bonnie R.; Heltshe, Sonya H.; Borowitz, Drucy
Abstract: Importance: Treatment recommendations for infants with CF standardize care, but most surveillance or treatment guidance of pulmonary manifestations are consensus‐based due to sparse evidence. Objective: To report observations about pulmonary correlates of growth and other clinical features in infants with CF. Methods: We analyzed data from the prospective Baby Observational and Nutrition Study conducted in 28 centers across the US, including clinical features, medications, guardian diaries of respiratory symptoms, oropharyngeal swab cultures and chest radiographs (CXR) collected over the first year of life. Results: Cough was reported in 84% of infants in the first year. Up to 30% had clinically important cough but only 6.3% had crackles; 16.5% had wheeze. Wisconsin CXR score was above 5 in 23% (normal = 0; maximum score = 100). Pseudomonas was recovered from at least one respiratory culture in 24% of infants and was associated with crackles/wheezes and use of proton pump inhibitors (PPI) (OR = 5.47; 95%CI = 1.36, 21.92; P = 0.02) or PPI plus histamine‐2 (H2) blocker (OR = 8.2; 95%CI = 2.41, 27.93; P = 0.001), but not H2 blocker alone. Hospitalization for respiratory indications occurred in 18% of infants and was associated with crackles/wheeze and abnormal CXR but not low weight, Pseudomonas or use of acid blockade. Conclusions: Cough is common in infants with CF, but few present with crackles/wheeze or CXR changes. Pseudomonas is associated with use of PPI or PPI plus H2 blocker, but not with respiratory hospitalization. These observations cannot prove cause and effect but add to our understanding of pulmonary manifestations of CF in infants. Trial Registration: United StatesClinicalTrials.Gov registry NCT01424696 (clinicaltrials.gov ).